Organizational Cultures In Supporting SMEs Competitiveness Within Indonesian Silk Industry - Latunreng, Wahyuddin; Hesti Wibowo, Daryanto (International Journal of Engineering and Technology, 2018)
This study aims to determine the role of organizational culture in the context of the competitiveness of small and medium enterprises (SMEs) in the silk industry in Indonesia. The case studies carried out in Wajo, South Sulawesi as one of Indonesia's leading silk producer. The influence of organizational culture on competitiveness is analyzed quantitatively and qualitatively through field survey. Respondents came from silk businesses and local governments, Regent, Head of the Department of Trade and Industry. Then it is compared to the SMEs practices in several countries in Asia: Japan, China and India. The results showed that the organizational culture of SMEs silk in Wajo district classified as 'good' so that it is a strong capital in the development of silk industry in this area. Marketing, development of product design, advanced technology and copyright need attention in increasing competitiveness as a consequence of the free market. The results of this study support the Indonesian government that has recently turned out to specifically instruct Wajo local governments in taking strategic decisions to spur growth in this industry sector.